W kierunku Biblioteki 2028 – zmiany w strukturze oraz zadaniach bibliotek akademickich na przykładzie Biblioteki Głównej Uniwersytetu Ekonomicznego we Wrocławiu - Kościewicz, Dawid (AUPC Studia ad Bibliothecarum Scientiam Pertinentia, 2019)
The goal of the paper is to discuss the changes in organization and the offer of library services, which are systematically introduced by the Main Library of the Wrocław University of Economics and Business, in response to the changes of the modern information technologies, expectations and needs of users and the realization of the ideal of continual improvement of the library services. The organizational changes for improvement of effectiveness and better professionalization of the library services as well as undertaken educational initiatives are discussed especially in the context of improving information literacy of the University’s employees regarding electronic sources of scientific information and bibliometric tools. The paper is based on the literature regarding the changes in the structure and objectives of an academic library, as well as the experiences and observations of the author.